2010
DOI: 10.1002/esp.1992
|View full text |Cite
|
Sign up to set email alerts
|

The topographic imprint of a transient climate episode: the western Andean flank between 15·5° and 41·5°S

Abstract: Mountain-range topography is determined by the complex interplay between tectonics and climate. However, often it is not clear to what extent climate forces topographic evolution and how past climatic episodes are reflected in relief. The Andes are a tectonically active mountain belt encompassing various climatic zones with pronounced differences in rainfall and glacier extent under similar plate-boundary conditions. In the Central to South-Western Andes climatic zones range from hyperarid desert with mean ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 103 publications
(155 reference statements)
1
30
0
Order By: Relevance
“…The rainfall gradient results in an increase in river network density and higher river transport capacity towards higher latitudes, resulting in more efficient fluvial sediment transport towards the ocean (Rehak et al, 2010). For turbidity currents to recur frequently, the ultimate amount of sediment that reaches the ocean at a river mouth is crucial, even though centennial to millennial erosion rates in the high-relief Andean catchments do not necessarily correlate with southward increasing precipitation, but rather with mean catchment slope (Carretier et al, 2013(Carretier et al, , 2014.…”
Section: Climatic Conditionsmentioning
confidence: 96%
See 2 more Smart Citations
“…The rainfall gradient results in an increase in river network density and higher river transport capacity towards higher latitudes, resulting in more efficient fluvial sediment transport towards the ocean (Rehak et al, 2010). For turbidity currents to recur frequently, the ultimate amount of sediment that reaches the ocean at a river mouth is crucial, even though centennial to millennial erosion rates in the high-relief Andean catchments do not necessarily correlate with southward increasing precipitation, but rather with mean catchment slope (Carretier et al, 2013(Carretier et al, , 2014.…”
Section: Climatic Conditionsmentioning
confidence: 96%
“…Even though precipitation decreases northward, millennialscale erosion rates in the Andean catchments peak due to steep average hillslopes (Carretier et al, 2013(Carretier et al, , 2014. Steeper hillslopes in the north are attributed to the fact that elevation and relief along the transient landscape of the western Andean flank between 16 and 41 S decrease with increasing rainfall (Rehak et al, 2010). High local relief between 28 and 35 S has been attributed to glacial erosion during the Quaternary and has not yet been obliterated due to inefficient fluvial drainage networks and inefficient hillslope processes.…”
Section: Most Suitable Areas For Paleoseismic Investigations Based Onmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Rehak et al (2010) suggest that the generation of local relief is a force balance between protracted fluvial erosion and glacial erosion acting as opposite agents; whereas glacial erosion appears to create local relief, persistent moderate rainfall above a critical threshold appears to smooth it. Figure 1.6 gives a general view of current geomorphological features of Chile, including principal transverse profiles east-west along continental territory.…”
Section: Territory Formation: Geology and Geomorphologymentioning
confidence: 96%
“…In order to diagnose the imprint of different climate zones on the relief of mountain ranges, Rehak et al (2010) correlated climate with relief parameters and investigated the impact of different geomorphological regimes on relief evolution. They concluded that the catchment-scale relief of the western flank of the Andean mountain chain distinctly reflects the dominant geomorphological process, which is determined by, and therefore represents, past and present regional climate regimes.…”
Section: Territory Formation: Geology and Geomorphologymentioning
confidence: 99%